Item Arrangement Pattern in Warehouse Using Apriori Algorithm (giant Kapasan Case Study) - Rifki Fahrial Zainal; Fardanto Setyatama (Fakultas Teknik Universitas Bhayangkara, 2016)
Giant is a retail company with supermarket format. Giant supermarkets should understand what are the items actually needed by their customers, particularly in easiness of choosing shop items. One of the method that can be used to analyze customer shopping behaviour pattern is analysis using the help of apriori algorithm. The analysis result, rules for item procurement are succesfully obtained. Rule that can be formed with minimum support and minimum confident highest values shows that the produced rule is Sedap Mie Rasa Ayam Spc 69g  Cleo Air Minum Extra Oxygen 550 ml. Based on the result, therefore Giant Kapasan should provide item Cleo Air Minum Extra Oxygen 550 ml when it sells Sedap Mie Rasa Ayam Spc 69g.